Interdisciplining digital humanities : boundary work in an emerging field - Klein, Julie Thompson (Digital humanities (Ann Arbor, Mich.), 2015)
The first book to test the claim that the emerging field of Digital Humanities is interdisciplinary and also examines the boundary work of establishing and sustaining a new field of study.